Kekuatan perlekatan geser semen ionomer kaca terhadap dentin dan NiCr alloy (Shear bond strenght of glass ionomer cement in dentin and NiCr alloy) - Mira Leonita; R. Iskandar (Dental Journal (Majalah Kedokteran Gigi), 2005)
Glass ionomer cements were used broadly in restorative dentistry. That’s why researchers always try to invent new form of glass ionomer cement. The newest invention was the paste-paste formulation. Shear bond strenght of powder-liquid glass ionomer cement and paste-paste glass ionomer cement in dentin and NiCr alloy was tested to 4 groups of samples. Each group consisted contain 6 samples that were shaped into cylinder with 4 mm of diameter and 5 mm of height. Group A was dentin with powder-liquid glass ionomer cement, group B was dentin with paste-paste glass ionomer cement, group C was alloy with powder-liquid glass ionomer cement, and group D was alloy with paste-paste glass ionomer cement. Each sample in each group was tested with Autograph. The datas were analyzed statistically using T-test with level of signficance 0.05. The result showed that powder-liquid glass ionomer cement shear bond strenght was 211 N and paste-paste glass ionomer cement was 166.92 N. That showed that powder-liquid glass ionomer cement had a better shear bond strenght.